Synthesis of Adipate Esters Using Candida Rugosa Lipase Immobilized Onto Layered Double Hydroxides - Zaidan, Uswatun Hasanah (2007)
The increasing demand for specially formulated adipate esters make it necessary to develop highly specific catalysts. For this reason, the application of immobilized enzyme as industrial biocatalyst for the synthesis of adipate ester via environmental benign process is undergoing a rapid development. Because of the unique and reproducible properties, layered double hydroxides (LDHs) were used as supports for enzyme immobilization. In this study, layered double hydroxides (LDHs) of Mg/Al-NO3-, Zn/Al-NO3- and Ni/Al-NO3- of molar ratio of M2+/M3+ (4:1) was prepared by co-precipitation method through continuous agitation. Their structures and characteristics were determined using X-ray Diffractometer (XRD), Accelerated of Surface Area and Porosimeter (ASAP), Fourier Transform Infra-red (FTIR) and Scanning Electron Microscopy (SEM). From the analysis results, the supports were found to be successfully synthesized. Lipase from Candida rugosa was immobilized onto these newly synthesized supports by a simple and inexpensive method of physical adsorption. Immobilization of lipase onto these support was confirmed using Energy Dispersion X-ray (EDX). EDX spectra of immobilized LDHs-lipase proved that immobilization process occurred based on the presence of both the metal compounds of the supports and protein components. The percentages of protein loading on LDHs were from 58 - 71%, due to the larger surface area (24.0 – 52.6 m2g-1), porosity (8.7 x 10-3 – 22.8 x 10-3 cm3g-1) and basal spacing (8.2 – 9.3 Ǻ) of the supports. The synthesis of dimethyl adipate (DMA) and dibutyl adipate (DBA) esters catalyzed by immobilized lipases were carried out via esterification of adipic acid and methanol as well as butanol as substrates and hexane as reaction medium. The effects of various reaction parameters such as reaction time, temperature, organic solvent, water activity and mole ratio of substrates were studied to determine optimal conditions for the production of adipate esters. The optimal conditions for both DMA and DBA esters syntheses using immobilized lipases were obtained at reaction time; 2.5 hours, temperature; 50 oC and molar ratio of substrates; 2. High yields (>65%) of the products were obtained in hexane (log P = 3.5) as the reaction medium and optimal percent conversion (up to 85%) was found to be dependant on the water activity (Aw) of 0.53 for DMA and 0.75 for DBA. The stability studies on the effects of thermal stability, leaching study, stability in organic solvent, storage study and reusability were investigated for their influence on the enzymatic esterification for production of adipates. The immobilized lipases retained high catalytic activity and showed increased stability compared to the native lipase in all cases. In thermal stability study, immobilized lipases were less affected and showed high activity even upon incubation at 70°C. When stored at different temperatures for 60 days, all immobilized lipases performed much better in activity. Furthermore, the commercial immobilized lipases and the LDHs-lipases showed an efficient reuse which makes this system attractive and applicable to various reactions.